2013
DOI: 10.7553/72-1-1376
|View full text |Cite
|
Sign up to set email alerts
|

Empowering the South African community's AIDS intervention workforce: an informetric study of HIV/AIDS research projects, with special reference to masters and doctoral dissertations and theses

Abstract: The prevalence rate of HIV in South Africa has maintained an alarmingly high level and has become a great concern for all stakeholders. The situation has demanded an increase in the number and strengthening of the HIV/AIDS intervention workforce to fight the pandemic. This has resulted in many individuals enrolling to undergo training in institutions of higher learning and the aftermath has been an increased number of graduates conducting research on various aspects of the disease. The purpose of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Table 4 indicates that most research was carried out at Masters level, which produced a total 163 (77%) records while the Doctoral research output totalled 48, accounting for 23% of total 210. A similar observation was made by Onyancha (2006) who cited that "[the] majority of studies were conducted at Masters Level of education while there was a favorable representation from the Doctorate candidates" in HIV/AIDS research in South Africa.…”
Section: Level and Qualification Of Post-graduate Iandkm Research In Sosupporting
confidence: 66%
See 2 more Smart Citations
“…Table 4 indicates that most research was carried out at Masters level, which produced a total 163 (77%) records while the Doctoral research output totalled 48, accounting for 23% of total 210. A similar observation was made by Onyancha (2006) who cited that "[the] majority of studies were conducted at Masters Level of education while there was a favorable representation from the Doctorate candidates" in HIV/AIDS research in South Africa.…”
Section: Level and Qualification Of Post-graduate Iandkm Research In Sosupporting
confidence: 66%
“…Although these values indicate some kind of relationship between the two databases' coverage of I&KM research, they nevertheless indicate that the contents of the databases are different as far as I&KM research by post-graduate research in South Africa is concerned. Onyancha (2006), too, observed that the coverage overlap ratio in HIV/AIDS research between the UCTD and C&CR was low and concluded that there were therefore differences as opposed to similarities in coverage of the contents of the two databases. It was also observed in the current study that C&CR yielded more records than UCTD.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informetrics is a method applicable in assessing, measuring and examining the pattern, impact and phenomenon of information produced in publications/literature, information sources and information retrieval processes (Onyancha 2006;Bar-Ilan and Peritz 2002;Diadato 1994). This study applied a descriptive informetric method which evaluates the publication count, characteristics and features of literature (Onyancha 2006). The method was used to examine and analyse articles on climate change published in the two newspapers under review.…”
Section: Methodsmentioning
confidence: 99%
“…For the literature on information provision and information sources for HIV/AIDS from the region see Onyancha (2006) and Onyancha and Ocholla (2006). Diko (2005) examined the use of billboards in the information campaign of LoveLife which sought to establish a new model of information provision targeted at reduction in high-risk sexual behaviour among young people.…”
Section: Studies On Information Provision and Information Sources Formentioning
confidence: 99%